(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The article discusses time management and its importance. The introduction highlights how crucial this topic is in today’s world. The literature review section analyzes research conducted on time-allocation technologies. Moreover, evidence about the significance of time-management techniques is provided, and the main aspects of effective time distribution are examined, followed by a conclusion.